Clinical Characteristics, Prognosis, and Nomogram for Esophageal Cancer Based on Adenosquamous Carcinoma: A SEER Database Analysis - Qian, Haisheng; Ji, Xiaofeng; Liu, Chang; Dang, Yini; Li, Xuan; Zhang, Guoxin (Frontiers in Oncology, 2021)
Objective: Esophageal adenosquamous carcinoma (ASC) is a rare pathological type with its clinical features and prognosis is poorly understood. The purpose of this study was to identify the characteristics of ASC patients and analyze the risk factors of esophageal carcinoma. Methods: Patients with esophageal cancer in the SEER database diagnosed from 1975–2016 were obtained. The epidemiology, clinical characteristics, and outcomes between these three groups were compared. The nomogram and online dynamic nomogram were constructed according to the Cox proportional hazard model. Results: The age-adjusted incidences of AC (1975-1999), AC(1999-2016) and ASC (1975-1989) increased over time (p < 0.05). Age-adjusted incidences of SqCC (1986-2012) and ASC (1989-2016) decreased (p < 0.05). Survival of patients with ASC was significantly worse when compared to AC and SqCC (ASC vs AC, p < 0.001, ASC vs SqCC, p = 0.01). ASC, older age, black race, male, overlapping site, higher tumor grade, lymph node metastasis, higher summary stage or AJCC stage were considered to be risk factors for poor survival in multivariate Cox analysis. The ROC curves and AUC indicated the model has a good discrimination ability (Figure 4B-C, AUC were 0.774 for 3-year OS and 0.782 for 5-year OS). An online dynamic nomogram was built based on Cox proportional hazard model for convenient clinical use. Conclusions: ASC is somewhat closer to AC rather than SqCC in term of demographics and tumor site, but has a worse OS than both AC and SqCC.